Efektivitas Teknik Self Management Untuk Menurunkan Hasrat Merokok Pada Siswa SMAN 1 Darul Imarah - Fitri Arnita; Abu Bakar; Nurbaity Bustamam (Program Studi Bimbingan dan Konseling, FKIP Universitas Syiah Kuala, 2018)
Smoking desire some character that must derived because it can carry people to be active smoker. The purpose of this study is to help decrease this desire in students of SMAN 1 Darul Imarah using self management techniques, also to prove if this technique bring significant changes before and after the students given treatment. This research type was an quantitative approach with pre-experimental study one group pre-post test design. Samples are 8 students from 44 students were selected by purposive sampling method. The research data were collected using questionnaire with 1-4 scale. Data were analyzed using paired-sample sign test-scale to prove there is decrease in the desire of smoking before and after treatment. The results of this research there was a significant score increase after treatment self-management techniques given to students, there are difference value of post-test lower than the pre-test of 70.37 ≤ 88.62. Which means, there is an decrease score in the score of smoking desire before and after given self management techniques. Decrease score before and after given treatment as much as 18,62. As for positive changes (+) or X as much as 8 therefore, by looking at the binominal table n = 8 and p = 0.5, then the probability for X≥8 is 0.004 and because 0.004 is smaller than 0.05 then the hypothesis testing in this research Ho is rejected. This means that there is a significant difference in smoking craving score from samples before and after given self management technique. It means this treatment was success in helping decrease somking desire in students of SMAN 1 Darul Imarah.Keywords : Smoking Desire, Self Management Technique